Estudo diacrônico do processo de expansão gramatical e lexical dos itens ter, haver, ser, estar e ir na Língua portuguesa - Sueli Maria Coelho (2006)
The grammatical expansion of the items TER, HAVER, SER, ESTAR e IR (HAVE, the equivalent to English there is/was, BE, GO) in Portuguese was investigated from a diachronic point of view. The process through which full verbs gradually take up grammatical functions, which allow them to move from the Lexicon to Grammar by forming verbal phrases, was studied from a quantitative methodology of grammaticalization within a formalist framework. At the same time, the semantic expansion/restriction which these verbs undergo diachronically was alsoanalyzed. The later, not only relates to grammaticalization of the form, but also to its (de)lexicalization process. To achieve the goals just mentioned, a corpora of twelve texts of varying textual genres was selected, so that each distinguishable period of the Portugueselanguage archaic, modern and contemporary was represented by four texts of about the same length. The criteria for analysis were divided into two interdependent groups: (a) an analysis of the items frequency and (b) a study of semantic, syntactic and morphophonemic factors. At first, the global frequency of occurrence of each selected verbal form was computed in each text. Then, their lexical frequency was tabulated, and contrasted to their grammatical frequency along the three periods, the statistical adherence test of Square-Qui having been used to measure the significance of the values obtained. Next, a semantic analysis of the registered lexical occurrences was carried on to identify the semas of each verbal form analyzed along the history of the language. The aim of such an analysis was to check the abstractness of the verb as itsgrammaticalization process evolves. After that, the syntactic contexts where the forms occurred were raised, so that the main factors determining the choice of forms that can co-occur with the auxiliary verbs in the verbal phrases were identified. Finally, some considerations were made on the loss of phonic material in items under grammaticalization. The attained results demonstrated that all five verbs analyzed are presently grammatical in Portuguese and so have been since thearchaic period; and that many of them are still in full expansion in the language. Moreover, the collected data led to the understanding that grammaticalization and lexicalization are linguistic processes that run parallel and, thus, do not define each other. Therefore, the fact that a certain verbal form is already grammatical does not hinder, nor favor its expansion and/or restriction in the domain of the Lexicon. Another generalization from the analysis undertaken is that verbal phrases result, not only from migration of items from the Lexion to Grammar, but also from a strengthening of the grammaticality of items that move on from a less grammatical stage to a more grammatical one.